1983
DOI: 10.1111/j.1600-0536.1983.tb04388.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro phototoxicity of different parts of Heracleum Laciniatum

Abstract: Experimental phytophotodermatitis was produced using homogenates from different parts of Heracleum laciniatum and long-wave ultraviolet light. The homogenates of leaves and flowers produced strong phototoxic reactions, fruit slightly less. Stems were either non-phototoxic or only slightly phototoxic. The roots of young plants did not evoke photosensitivity reactions, whereas the roots of older plants were strongly phototoxic; even roots collected from the frozen ground in December elicited strong reactions. Ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
3

Year Published

1986
1986
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 8 publications
1
6
0
3
Order By: Relevance
“…Their level is maximal in the fruit, intermediate in the leaf and minimal in the stem. Our findings are consistent with those in the literature (6) reporting stronger phototoxic reaction for leaves, flowers and fruits than for stems of Heracleum laciniatum.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Their level is maximal in the fruit, intermediate in the leaf and minimal in the stem. Our findings are consistent with those in the literature (6) reporting stronger phototoxic reaction for leaves, flowers and fruits than for stems of Heracleum laciniatum.…”
Section: Resultssupporting
confidence: 93%
“…These cases happen predominantly in the spring-summer season, probably both due to the increase in linear furocoumarins of the weed itself and to the stronger ultraviolet rays (5). The linear furocoumarins of H. mantegazzianum have been studied to date only biologically, using Daniels' method which evaluates the inhibition of Candida albicans growth (6). This method gives a semiquantitative evaluation of the total furocoumarin content, without separating the various components (5).…”
mentioning
confidence: 99%
“…The affected part of the skin can develop blisters (Kavli et al 1983b) followed by high melanin production (hyperpigmentation) that can last for several months (Kavli et al 1983a). Children playing outdoors and people working outside, such as gardeners, are especially in danger of exposure to Heracleum sap (Nielsen et al 2005 (EPPO/OEPP 2009;Nielsen et al 2005).…”
Section: Management Implicationsmentioning
confidence: 99%
“…Aside from Tromsø palm's impact on other plant species, its sap contains furocoumarins (Kavli and Volden 1984) that, in combination with UV radiation (e.g., from the sun), lead to a phototoxic reaction that burns human skin (photodermatitis) (Kavli et al 1983b). The affected part of the skin can develop blisters (Kavli et al 1983b) followed by high melanin production (hyperpigmentation) that can last for several months (Kavli et al 1983a).…”
Section: Management Implicationsmentioning
confidence: 99%
“…The best long-wave ultraviolet light that produced PPD was identified in the range 315-375 nm, with peak sensitivity at 330-335 nm, therefore, within the ultraviolet A spectrum [34] . Subsequently, the same authors identified the flowers and leaves as the best parts to trigger PPD [35] . Several animal models have been used to investigate the phototoxic reactions to medications [36][37][38][39][40] .…”
Section: E X P E R I M E N T a L S T U D I E S O N P P D Reproductionmentioning
confidence: 99%